A novel low-frequency multi-bandgaps metaplate: Genetic algorithm based optimization and experimental validation. (1st December 2022) - Panahi, Emad; Hosseinkhani, Ali; Frangi, Attilio; Younesian, Davood; Zega, Valentina
Abstract: Metaplates, i.e. 2D extruded structures made by a periodic repetition of unit cells that exhibit a complete and wide 3D bandgap, are attracting increasing interest thanks to the variety of emerging applications. In this work, an innovative planar unit cell suitable for metaplates is proposed and optimized through a genetic algorithm, to achieve wide and low frequency bandgaps. Four objective functions are employed to show the potentiality of the proposed topology with respect to the state of the art. Metaplates obtained through the periodic repetition of the optimized unit cells are then simulated and experimentally tested. High performance metaplates, endowed e.g. with a nondimensional opening frequency of 0.0029 and bandgap width equal to 95%, are here obtained, thus opening the path to challenging applications also in the world of Micro-Electro-Mechanical Systems (MEMS).